2019
DOI: 10.1016/j.ijdevneu.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of DAPK1 in neuronal cell death, survival and diseases in the nervous system

Abstract: DAPK (death‐associated protein kinase) is a calcium/calmodulin (Ca2+/CaM) regulated serine/threonine kinase. Structurally, it assumes a multi‐domain structure and participates in various apoptotic systems which imply that it may interact with a wide range of intracellular components to exert its action. DAPK plays vital roles in pro‐apoptotic, apoptotic and autophagic pathways. In addition, it plays important roles in many diseases such as cancer, Alzheimer's disease, cerebral ischemia and epilepsy. Although a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 117 publications
(162 reference statements)
0
12
0
Order By: Relevance
“…Death-associated protein kinase 1 (DAPK1), as a serine/threonine (Ser/Thr) kinase, plays a critical role in the regulation of stress-induced cell death [6,7]. DAPK1 is a pro-apoptotic gene that stimulates cellular apoptosis in response to multiple internal and external apoptotic stimuli [8,9,10]. This pro-apoptotic Ser/Thr kinase is involved in caspase-dependent (i.e., apoptosis) and caspase-independent cell death processes [6,7,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Death-associated protein kinase 1 (DAPK1), as a serine/threonine (Ser/Thr) kinase, plays a critical role in the regulation of stress-induced cell death [6,7]. DAPK1 is a pro-apoptotic gene that stimulates cellular apoptosis in response to multiple internal and external apoptotic stimuli [8,9,10]. This pro-apoptotic Ser/Thr kinase is involved in caspase-dependent (i.e., apoptosis) and caspase-independent cell death processes [6,7,10].…”
Section: Introductionmentioning
confidence: 99%
“…DAPK1 is a pro-apoptotic gene that stimulates cellular apoptosis in response to multiple internal and external apoptotic stimuli [8,9,10]. This pro-apoptotic Ser/Thr kinase is involved in caspase-dependent (i.e., apoptosis) and caspase-independent cell death processes [6,7,10]. In addition to its role in cell death, DAPK1 has been implicated in the cell cycle, tumorigenesis, tumor metastasis, inflammation, oxidative stress and neurodegeneration [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…DAPK1 is widely known as a tumor suppressor that modulates cell survival and death in a variety of cell systems. Moreover, accumulating evidence has shown that apoptotic neuronal death is regulated by DAPK1, and defective DAPK1 function is associated with NDDs [19,21,22,30]. For example, DAPK1 plays a role in brain stroke by interacting with NMDA receptors [41].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of DAPK1 increases formation of autophagic vesicles during programmed cell death [18]. Recent evidence suggests that DAPK1 regulates cell death in the brain, and that the alteration of kinase activity is closely associated with NDDs [19]. For example, DAPK1 activation induces the phosphorylation of p53 at Ser23 [20], increasing apoptotic neuronal cell death [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Since this discovery, DAPK1 has attracted extensive attention as a potential risk factor for LOAD. DAPK1, a Ca 2+ /CaM-dependent serine/threonine protein kinase, plays a critical role in death signaling (proapoptotic, apoptotic and autophagic pathways) and the regulation of internal and external stress-induced cell damage, including ischemia and Aβ [124][125][126], which implies that it may have a role in various neuropathologies, such as AD, ischemia, and epilepsy. The critical role of DAPK1 in AD was confirmed at the cellular and animal levels [127,128], and it is currently believed that DAPK1 may be a key player in mediating the pathological process of dementia.…”
Section: Dapk1mentioning
confidence: 99%